Knee Spine Syndrome Mechanism in Knee Osteoarthritis: Review Article - I Made Buda Kurniantara; Gusti Ayu Alit Triwahyuni (Physical Therapy Journal of Indonesia, 2020)
Introduction: Osteoarthritis (OA) is the most common arthritis and one of the main causes of disability. This injury can occur in any joint, but the most common OA occurrence globally, especially in Indonesia, is Knee OA (KOA). Damage caused by KOA's degenerative process affects the knee and affects the surrounding structures, such as the lumbar vertebra, which increases symptoms of low back pain (LBP). The occurrence of symptoms of LBP is thought to be caused by knee spine syndrome, which is a condition reduced lumbar lordosis angle due to the degenerative phase of KOA. the mechanism of this syndrome has not yet been discussed in detail, so further discussion is needed in the future. Methods: We searched articles using a list of keywords, including "knee osteoarthritis and low back pain", "knee osteoarthritis and knee contracture", "knee contracture and muscle weakness", "knee contracture and spinal alignments", "knee osteoarthritis and spinal alignment", "knee osteoarthritis and sagittal spinal alignment", and "muscle activation and spinal imbalance" on the data sources of PubMed, ScienceDirect, and Google Scholar. The argumentative, descriptive analysis was used for the data analysis technique. Results: Based on the literature search, the author found four related articles. This study provides evidence of the effect of KOA on lumbar proprioception. These articles explained that an impact on knee posture could have long-term effects both in the spine and pelvis, such as lumbar lordosis. Conclusion: Knee spine syndrome results from a reduced angle of lumbar lordosis, increasing pressure between discs, which might increase LBP symptoms. In the future, it is hoped that there will be studies that raise the relationship between KOA and symptom of LBP.